Structural Model Of Economic Growth On The Island Of Java - M. Aliyuddin; Etty Soesilowati; Tri Wahyu Hardaningrum (Citakonsultindo, 2025)
Structural transformation is an important topic in the literature on economic growth. Recent research identifies various paths of structural transformation in developing countries, emphasising that the key to growth is the shift of labour from agriculture to manufacturing and services. Input-output analysis of 17 sectors can identify sectors with important roles on the island of Java. The type and design of this research use a descriptive quantitative approach. The results of this study show that the key sectors are played by three sectors, namely sector 4 (electricity, gas and ice production), sector 8 (transportation and warehousing), and sector 13 (business services), because these sectors have strong backward and forward linkages. Therefore, it is important to support these key sectors as well as other economic sectors for the sustainability of Java's economic transformation, particularly in increasing the output multiplier, income multiplier, and employment opportunity multiplier, through support such as investment, both domestic investment (PMDN) and foreign investment (PMA). Furthermore, to sustain economic growth on the island of Java, support is also needed for international trade, with a focus on labour productivity and technology